Endografts for the treatment of abdominal aortic aneurysms with a hostile neck anatomy: A systematic review - Pitros, Christos; Mansi, Pietro; Kakkos, Stavros (Frontiers in Surgery, 2022)
Background: Endovascular Aortic Repair (EVAR) of abdominal aortic aneurysms (AAAs) has emerged as a better alternative to conventional open surgery for AAAs. The purpose of the review is to define the improvement in the clinical management of the patient with hostile neck AAAs due to the introduction of new endografts, while giving a thorough description of their instructions for use (IFU), main characteristics and part sizing, reporting their outcomes from clinical studies and categorizing their usability. Methods: A MEDLINE search was conducted using keyword specific combinations. Clinical studies were searched via clinicaltrials.gov website. Relevant articles’ references were also hand-searched. Results: We retrieved 640 records describing Alto, Ovation iX, Treovance, Aorfix, Anaconda, Conformable, and Endurant II/IIs endografts. Aortic necks >60° can be managed with Anaconda, Aorfix and Conformable that can treat up to 90° necks requiring ≥15 mm (Anaconda ≥20 mm) necks and Treovance which is eligible for necks ≤ 75° with ≥15 mm length. The Ovation’s innovation of combining polymer filled O-rings with integral anchors can treat conical necked AAAs giving Ovation iX and Alto an advantage. Short necked AAAs can be treated with Alto, eligible for necks as short as 7mm and Endurant II which can treat ≥10 mm necks or 4 mm if used in conjunction with EndoAnchors system, respectively. Alto and Conformable report 100% technical success rate, absence of AAA related death, migration, ruptures and limb occlusion during follow-up. Endurant II and Ovation iX report >99% technical success rate, are almost free from AAA mortality rate, ruptures, migration and limb occlusion, while Ovation iX has a high rate of sac dilation (15.5%) in 5-year follow up. Anaconda just over Aorfix and Treovance which are related to the lowest technical success rate, 98.3%, 96.3%, 96% respectively. Aorfix has highest AAA mortality rate, 4% in 60 months follow-up. Conclusion: Most new generation endografts described have comparable results. They broaden the eligibility of patients for EVAR due to their unique technical characteristics described. There is lack of comparative studies for newer endografts and post-market clinical studies with long-term results concerning the most recently approved devices described, Alto and Conformable.